Prognostic significance of the prominent vein sign on susceptibility-weighted imaging for collateral circulation assessment in acute large vessel occlusion stroke: a systematic review and meta-analysis - Krishnan, Ponnarasan; Tharek, Anas; Al-Akmal Noralam, Noor Hayatul; Shamsuddin Perisamy, Rajeev; Muda, Ahmad Sobri (Tianjin University, 2025)
Acute ischemic stroke (AIS) due to large vessel occlusion (LVO) presents significant challenges in clinical management, with collateral circulation playing a pivotal role in determining tissue viability and patient outcomes. Susceptibility-weighted imaging (SWI) has emerged as a valuable non-invasive modality for assessing cerebral hemodynamics by visualizing the prominent vein sign (PVS), which reflects increased deoxyhemoglobin concentration and oxygen extraction in hypoperfused brain regions. This synthesis examines the pathophysiological basis, prevalence, and imaging characteristics of PVS, highlighting its correlation with leptomeningeal collateralization and its prognostic significance in both short- and long-term functional outcomes. Comparative analyses with other imaging techniques, including diffusion-weighted imaging (DWI), perfusion-weighted imaging (PWI), magnetic resonance angiography (MRA), and computed tomography angiography (CTA), underscore the complementary role of SWI in collateral assessment. The integration of quantitative and qualitative PVS evaluation methods enhances the accuracy of collateral grading and supports individualized treatment planning, particularly in selecting candidates for recanalization therapies. Challenges related to technical variability, interpretative subjectivity, and confounding clinical factors are addressed, emphasizing the need for standardized imaging protocols and robust validation. Emerging technological innovations and advanced analytic approaches promise to refine collateral imaging further, facilitating personalized stroke therapy. Incorporating PVS assessment into routine clinical workflows offers a non-contrast, accessible tool to improve prognostication and optimize therapeutic strategies in acute LVO stroke management.